Early detection of fibrotic areas in anterior STEMI by echocardiography. A case report - Siniscalchi, Carmine; Gaibazzi, Nicola (Acta Biomedica Atenei Parmensis, 2020)
We describe the case of a patient admitted to our ward for dyspnea and chest pain. Acutely performed electrocardiogram confirms the clinical suspect of myocardial infarction by showing ST-elevation in the anterior leads (STEMI). Primary percutaneous coronary intervention (PCI) was performed, with normal final coronary artery flow. At 6-month cardiac magnetic resonance (CMR) late Gadolinium enhancement (CMR-LGE) was present in the entire left anterior descending coronary artery territory. We also performed a standard echocardiogram on day 1 after primary angioplasty, as expected showing akinesia in the STEMI territory. Interesting, using a new echocardiographic setting, we have been able to very early detect fibrotic tissue in an easy and cost-effective way.